AL-MARAGHI’S EXEGESIS AND THE CONCEPT OF ISLAMIC PARENTING: AN EXAMINATION OF ISLAMIC EDUCATIONAL VALUES IN THE FAMILY - Laely Nurhayati; Enjang Burhanudin Yusuf (Jurnal Konseling Pendidikan Islam, 2026)
The family is the primary and most influential institution in a child’s educational development, where Islamic values are deeply instilled through parenting patterns rooted in the Qur’an and the Sunnah. In this context, Tafsir al-Maraghi by Ahmad Musthafa al-Maraghi holds a significant role as it presents rational, contextual, and educationally rich interpretations of the Qur’an. This study aims to examine the concept of Islamic parenting within Tafsir al-Maraghi and to explore Islamic educational values applicable to family life. This research employs a library research method with a thematic (maudhū‘i) approach and content analysis. The primary source is Tafsir al-Maraghi, supported by secondary sources from Islamic education and family psychology literature. The findings reveal four fundamental pillars of education in Tafsir al-Maraghi: monotheistic education (tauhid), parental moral exemplarity, affection and communication within the family, and the habituation of worship and social responsibility. These values align with contemporary Islamic parenting principles emphasizing the balance between love, discipline, and spirituality.